Phase II metabolism - Daly, Ann (Henry Stewart Talks, 2007)
Phase II metabolism, Conjugation of drugs and other xenobiotics with a range of different molecules including glucuronic acid, sulfate, amino acids, acetyl groups, methyl groups and glutathione, Properties of the enzyme families catalyzing these conjugation reactions, Typical drug-based examples of individual reactions, Genes encoding Phase II enzymes, Functionally significant polymorphisms and their effects
Reviewed at 2022/04/12